The potential for sustainable biomass in the Romanian energy sector. Value chain analysis for potential black pellets investments - Birgen Cansu; Matei Marius; Sannan Sigurd; Stamule Tănase (Management şi Marketing)
A value chain analysis was conducted to assess the potential of substituting coal with black pellets for energy production in Romania, including an evaluation of feedstock availability. The biomass production landscape in Romania is evolving due to rising demand and a growing number of pellet producers competing for raw materials. This shift is also driven by a decline in wood processing and exploitation activities, primarily due to reduced access to forest resources, legislative instability, and administrative complexities. Romania harvests 19 million cubic meters of wood annually, utilising only 50% of its sustainable harvesting capacity, which is equal to the natural growth rate of its forests. The operational costs for the value chains involved in power generation from black pellets and coal in a 50 MW power plant were also estimated. For the black pellets value chain, the annual operational costs are approximately 100.68 million lei–more than five times higher than the estimated 18.18 million lei for coal. This significant cost difference arises from higher expense of biomass harvesting compared to coal mining. The black pellets value chain also involves biomass pretreatment and steam explosion processes, which require electricity for feasibility. Additionally, the higher ash content of coal could increase the overall expenses due to ash disposal costs, although these costs were not included in this analysis.